Pelatihan Mahasiswa dalam Menggunakan Aplikasi Quizwhizzer Sebagai Media Evaluasi Interaktif - Ekaputra, Firdiawan (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
The development of technology that makes everything easy has an impact on the world of education. The existence of artificial intelligence makes new challenges for lecturers and teachers in creating interesting and interactive learning. Equipping students in developing and using interactive learning media is needed as an effort to keep up with the times and create meaningful learning. The purpose of this activity is to train students in using the quizwhizzer application as an interactive evaluation media. The methods used in this activity include training preparation, training implementation, and training evaluation. Based on the evaluation results, students benefit from the activities that have been carried out. Students have the ability to develop and use the quizwhizzer application as an interactive evaluation media. This can be a provision for students in creating interactive learning in internship activities and after graduating from lecture activities. The magnitude of the impact of provision to students in the form of training activities that have been carried out, it is recommended that similar training activities be carried out using other evaluation applications.